Komposisi Asam Amino Dari Ekstrak Kecambah Kacang Merah (Phaseolus vulgaris L) Setelah Tahap Deproteinasi - Adhi Suastuti, N. G. A. M. Dwi; Awalia Ramadhani, Amanda; Laksmiwati, A.A. I. A Mayun; Ratnayani, Ketut (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2022)
During the germination process, there is a degradation activity of reserve proteins in the seeds and releases short peptides and free amino acids. This study aimed to determine the amino acid composition of the red bean sprout extract after the deproteination stage. The deproteination stage is the stage of eliminating protein macromolecules that are dissolved in the extract so that short peptides and free amino acids are left in the extract. Red bean seeds were first germinated, made into flour, and extracted with distilled water, then deproteinized by the isoelectric precipitation method at pH 4.5. This protein macromolecular free extract(expected to contain free amino acids and short peptides) was then analyzed for its amino acid composition by the HPLC method. The results of the analysis of the composition of 15 types of amino acids in red bean sprout extract showed that the highest amino acid content was glutamic acid (1213,305 mg/kg), while the lowest amino acid content was tyrosine (118,245 mg/kg). The results also show phenylalanine as a type of essential amino acid with the highest levels compared to other essential amino acids. This shows that red bean sprout extract has the potential as a source of essential amino acids.